Hypermethylation of the glutathione peroxidase 4 promoter predicts poor prognosis in patients with hepatitis B virus-associated acute-on-chronic liver failure - Su, Xing; Han, Li-Yan; Wang, Jing; Zhang, Ying; Luo, Peng-Yu; Gao, Shuai; Fan, Yu-Chen; Wang, Jing-Wei; Wang, Kai (Frontiers in Molecular Biosciences, 2024)
Background: Hepatitis B virus-associated acute-on-chronic liver failure (HBV-ACLF) is a syndrome with a high short-term mortality rate, and its prognosis is critical in clinical management. This study aimed to investigate the clinical significance of glutathione peroxidase 4 (GPX4) in the occurrence and development of HBV-ACLF and its prognostic value for 90-day mortality.The expression levels of GPX4, oxidative stress-related molecules and inflammatory cytokines in serum or peripheral blood mononuclear cells (PBMCs) of 289 participants were determined by RT-qPCR or ELISA, and the methylation level of GPX4 promoter in PBMCs was determined by MethyLight.The expression levels of GPX4 in the PBMCs and serum of HBV-ACLF patients were lower than those in non-HBV-associated acute-on-chronic liver failure (non-HBV ACLF) patients, patients with chronic hepatitis B (CHB) and healthy control (HC) individuals, while the methylation level of the GPX4 promoter was greater. In HBV-ACLF patients, the methylation level of the GPX4 promoter is correlated with oxidative stress, inflammation-related molecules, and some clinicopathological indicators. The methylation level of the GPX4 promoter was identified as an independent risk factor for 90-day mortality in HBV-ACLF patients and yielded a larger area under the receiver operating characteristic curve (AUROC) than the model for end-stage liver disease (MELD) score in predicting 90-day mortality.The GPX4 promoter methylation level has promising potential as a predictor of 90-day mortality in patients with HBV-ACLF.